2018
DOI: 10.5114/wiitm.2018.73357
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for prolonged hospitalization in patients undergoing laparoscopic adrenalectomy.

Abstract: IntroductionEven though laparoscopic adrenalectomy is currently a standard, there are important variations between different centres in short-term treatment results such as length of hospital stay (LOS) or morbidity.AimTo determine the factors affecting LOS in patients after laparoscopic transperitoneal lateral adrenalectomy (LTA).Material and methodsThe study enrolled 453 patients (173 men and 280 women, mean age 57 years) who underwent LTA between 2009 and 2017. Discharge from hospital after more than median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…With respect to postoperative hospital stay, studies indicated that postoperative drainage also prolongs (24,35,36). Our results were in line with them.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to postoperative hospital stay, studies indicated that postoperative drainage also prolongs (24,35,36). Our results were in line with them.…”
Section: Discussionsupporting
confidence: 91%
“…In their series, they found that tumor size was not associated with longer operative times or hospital LOS [29]. Pisarska et al also found in their large series that the size of the tumor did not affect the LOS [30]. In our study mean operation time for lesions ≥ 6 cm was 177 min, which was significantly longer than for smaller lesions (p = 0.01).…”
Section: Discussionsupporting
confidence: 45%
“…Secondary outcomes included discharge disposition, health resource utilization as measured by the hospital length of stay (LOS) and total hospitalization charges between patients with and without blood transfusion. Longer LOS was defined as a LOS greater than or equal to the median for LOS, within the hospitalization for burn injury 21,22 . We also examined the trend of blood transfusion in patients with severe burn as a descriptive outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Longer LOS was defined as a LOS greater than or equal to the median for LOS, within the hospitalization for burn injury. 21,22 We also examined the trend of blood transfusion in patients with severe burn as a descriptive outcome.…”
Section: Study Outcomesmentioning
confidence: 99%